2017
DOI: 10.17576/jskm-2017-1502-06
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hanen More Than Words Programme on Parents of Children with ASD in Malaysia

Abstract: This study aims to investigate the viability and effectiveness of the Hanen More Than Words (HMTW) programme amongst parents of children with Autism Spectrum Disorder (ASD). This quassi-experimental study involved 31 children (27 boys, 4 girls; M = 34.58 months, SD = 3.67) who met criteria for ASD and their parents. The measurement was conducted in three phases; Time 1 (prior to intervention), Time 2 and Time 3 (at three and five months after the intervention begins). The outcome measures were assessed based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Kaiser, T.B. Hancock, unpublished data, 1998) . Articles were excluded because of the reported age of participants (mean age plus 1 SD, >6 years; n = 11 studies), the inclusion of too few participants (n = 34 studies), the inclusion of nonparents as the primary interventionists (n = 343 studies), no reported measure of communication or language (n = 66 studies), no availability in English (n = 8 studies), or no reported statistics appropriate for calculating an effect size and no additional details or no author response to a request for information (n = 226 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Kaiser, T.B. Hancock, unpublished data, 1998) . Articles were excluded because of the reported age of participants (mean age plus 1 SD, >6 years; n = 11 studies), the inclusion of too few participants (n = 34 studies), the inclusion of nonparents as the primary interventionists (n = 343 studies), no reported measure of communication or language (n = 66 studies), no availability in English (n = 8 studies), or no reported statistics appropriate for calculating an effect size and no additional details or no author response to a request for information (n = 226 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies reported intervention settings and 9 were conducted at home. Non-home settings include clinics (Allam et al, 2008;Bello-Mojeed et al, 2016;Krishnan et al, 2016;Rahman et al, 2015;Sokmum et al, 2017), classroom and school (Hu, et al, 2019;Travis & Geiger, 2010), and rehabilitation or autism centers (Piravej et al, 2009;Vadivel & Missal, 2014). This review coded "intervention dosage" as intervention duration and intensity.…”
Section: Intensity Settings and Dosagementioning
confidence: 99%
“…A single study that had multiple primary child outcomes were double counted. Outcomes included: social communication competency (Divan et at., 2019;June et al, 2012;Olcay-Gui &Tekin-Iftar, 2016;Perera et al, 2016;Rahman et al, 2015;Sokmum et al, 2017), general/comprehensive developmental skills (Pajareya &Nopmaneejumruslers, 2011;Petrovska & Trajkovski, 2019;Vadivel& Missal, 2014;Zhou, et al, 2018), behavioral challenges (Barkaia et al, 2007;Bello-Mojeed et al, 2016;Karanth et al, 2010;Travis & Geiger, 2010), language and communication skills (Allam et al,2008;Lai &Bali, 2007;Sokmum et al, 2017), autism symptoms (Divan et at., 2019;Krishnan et al, 2016;Piravej et al, 2009), adaptive skills (Divan et al, 2019;Krishnan et al, 2016), academic skills (visual matching skills) (Hu et al, 2019), cognitive skill (Allam et al, 2008), and leisure (gaming skills) (Catttik & Odluyurt, 2017).…”
Section: Intervention Outcomesmentioning
confidence: 99%
See 2 more Smart Citations